ANALISIS FAKTOR PERSEPSI YANG BERPENGARUH TERHADAP MINAT BELI KONSUMEN UNTUK BERBELANJA DI PASAR SEMI MODERN (Studi Pada Pasar Sampangan baru Semarang) - Febri Andrean, 12.05.51.0073; Maskur, Ali (Students Journal of Economic and Management, 2016)
This study aims to analyze empirically the perception of service, price perception, the perception of location, comfort perception, the perception of the completeness of the product and the perception of the quality of products on consumer buying interest for shopping at Pasar Baru Sampangan Semarang. The population in this study is that consumers who ever bought Sampangan Pasar Baru in Semarang. Sampling was done by using purposive sampling method and number of samples to be processed into the research data of 100 questionnaires. Data were analyzed using multiple linear regression model The results showed that the price perception, perception and perceived comfort range of products positif significantly influence consumer purchase interest for shopping at Pasar Baru Sampangan Semarang. While perceptions of service, location and the perception of product quality perception does not significantly influence buying interest. Keywords: Perception of Services, Perception Price, Perception Location, Convenience Perception, Perception Fittings Product, product quality perception and Interests Buy